1982
DOI: 10.1144/gsjgs.139.4.0455
|View full text |Cite
|
Sign up to set email alerts
|

The plate tectonic setting of NW Britain and Ireland in late Cambrian and early Ordovician times

Abstract: Deposition of Dalradian sediments in a stretching ensialic basin peripheral to Iapetus continued into Cambrian times. Late in the history of Dalradian deposition a southern continental landmass was removed by strike-slip motions and a subduction zone then developed beneath the Dalradian sediments. Deformation and moderately high pressure metamorphism of Dalradian rocks occurred and was followed by thermal relaxation and development of a volcanic arc with magmatic centres in Connemara by Tremadoc times and in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Although the onset of sedimentation remains poorly dated, it can now be reasonably suggested that sedimentation in this area ended in the Llanvirn. This would be consistent with many other areas on the northwest margin of Iapetus (Yardley et al 1982;Dewey ef al. 1983).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the onset of sedimentation remains poorly dated, it can now be reasonably suggested that sedimentation in this area ended in the Llanvirn. This would be consistent with many other areas on the northwest margin of Iapetus (Yardley et al 1982;Dewey ef al. 1983).…”
Section: Discussionsupporting
confidence: 91%
“…e.g. Harland et al 1982 (478 Ma); Gale et al 1979 (464 Ma);Churkin et al 1977 (467 Yardley et al (1982) who argue that Connemara was a root zone for a volcanic arc during the early Ordovician. Spatial association with South Mayo is based largely on correlations of the Lough Nafooey Group of basic volcanic rocks ( Figure 11) with intrusions in Connemara, both of which show increasing acidity with time.…”
Section: Discussionmentioning
confidence: 99%
“…The Bohaun volcanic rocks were extracted from an immobile element depleted mantle source. These may have been stripped from the roof to the Connemara block whose metamorphism is characteristic of the root of an island arc (Yardley, 1980;Yardley, Vine & Baldwin, 1982;Yardley, Barber & Gray, 1987). comms, 1994-95).…”
Section: A Pre-llandeilo Evolutionmentioning
confidence: 99%
“…Thirlwall (1981) interpreted the variation in certain chemical parameters of the Old Red volcanic rocks north of the Southern Uplands fault in this way, and Brown, Thorpe & Webb (1984) have shown that several large plutons in the Northeast Grampians have compositions comparable to those from modern mature continental arcs. But, as Thirlwall (1981), Yardley, Vine & Baldwin (1982) and others have pointed out, if analogies with modern arcs are valid, subduction at a trench located along the present trace of the Iapetus suture cannot account for Newer Granite intrusions further south than the Highland Border. The arc-trench gap in modern examples is normally greater than 90 km in width and often 150 km or more, so even allowing for tectonic shortening and some strike-slip erosion, it is clear that granites in the Southern Uplands could not represent the products of subduction along the Solway Line.…”
Section: A P E T U Smentioning
confidence: 84%